(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Even with all of the new and old therapies available, seizure management is infamously difficult. Scientists will continue to search for novel drugs with high selectivity and low central nervous system side effects in the hopes of finding the newest and most effective treatment. This work designates the synthesis of several 4- quinazolinones substituted with oxadiazoles and benzothiazoles through condensation of 2-substituted-4H-benzo(1,3)-oxazin-4-ones with substituted-oxadiazole and 6-substituted-benzothiazol-2-amine. The title compounds were confirmed through IR, 1H-NMR, 13C-NMR analyses. The compounds evaluated for anticonvulsant activity. Compounds A3, A4, A9, A5, A10 possess good potential. They reduce the extent of tonic phase up to 1.3 to 1.1 seconds and stupor up to 100 to 51 seconds with absence of straub phase when compared to the control group.